Assessing Student Engagement With Campus Chaplains: A Pilot Study From a Residential Liberal Arts College. Issue 3 (2nd August 2021) - van Stee, Elena G.; Paige Winfield, Taylor; Cadge, Wendy; Schmalzbauer, John; Steinwert, Tiffany; Rambo, Shelly; Clifford, Elizabeth
Abstract: This article examines student engagement with chaplaincy services through a pilot survey administered at a private liberal arts college ( n = 1043). Almost half of the respondents reported engagement with campus chaplains, which varied by religious tradition and race. Respondents who had engaged with chaplains were more likely to report integrating spirituality into daily life, feeling supported in wrestling with life's big questions, and experiencing spiritual growth. They were not more likely to feel they were resilient or could manage stress. The authors encourage researchers to build on the model and findings presented here to identify empirically how chaplaincy services affect students.